The influence of heating and cooling on the precision and microstructure of 3D printing results with PLA+ material - Hutauruk, Dikky Antonius; Tondang, Steven Austin (Politeknik Negeri Lhokseumawe, 2024)
The objective of this research is to investigate the influence of heating and cooling parameters on the accuracy and microstructure of 3D-printed products. Experimental methods were conducted by varying the heating and cooling parameters using PLA+ as the material. The results demonstrate that the heating and cooling parameters of the printing process significantly affect the precision and microstructure of 3D printed objects. Specimen printing was carried out using Ultimaker Cura 5.1.0 with a 100% infill density. Printing temperatures were set between 200°C and 240°C, with two variations of fan speeds at 80 mm/s and 100 mm/s. Other process parameters were kept constant, including a build plate temperature of 60°C, a grid infill pattern, and a printing speed of 50 mm/s. Three specimens were printed for each combination of fan speed and printing temperature. The printed specimens were measured using calipers, and then subjected to heating and cooling at different room temperatures before being measured again. The smallest average deviation was observed at a nozzle temperature of 240°C with fan speeds of 80% and 100%, specifically in specimens B-09 (with a bolt height of 17.60 mm, head diameter of 12.70 mm, bolt shaft diameter of 6.40 mm, and head thickness of 4.80 mm) and B-10 (with a bolt height of 17.60 mm, head diameter of 12.80 mm, bolt shaft diameter of 6.40 mm, and head thickness of 4.80 mm). Meanwhile, the microstructure analysis revealed that excessively high temperatures during the process could lead to increased deviations due to a structure resembling melting.